Contemporary Solutions for the Treatment of Facial Nerve Paralysis. Issue 6 (June 2015) - Garcia, Ryan M.; Hadlock, Tessa A.; Klebuc, Michael J.; Simpson, Roger L.; Zenn, Michael R.; Marcus, Jeffrey R.
<x xml:space="preserve">Abstract</x> Learning Objectives: After reviewing this article, the participant should be able to: 1. Understand the most modern indications and technique for neurotization, including masseter-to-facial nerve transfer (fifth-to-seventh cranial nerve transfer). 2. Contrast the advantages and limitations associated with contiguous muscle transfers and free-muscle transfers for facial reanimation. 3. Understand the indications for a two-stage and one-stage free gracilis muscle transfer for facial reanimation. 4. Apply nonsurgical adjuvant treatments for acute facial nerve paralysis. Summary: Facial expression is a complex neuromotor and psychomotor process that is disrupted in patients with facial paralysis breaking the link between emotion and physical expression. Contemporary reconstructive options are being implemented in patients with facial paralysis. While static procedures provide facial symmetry at rest, true "facial reanimation" requires restoration of facial movement. Contemporary treatment options include neurotization procedures (a new motor nerve is used to restore innervation to a viable muscle), contiguous regional muscle transfer (most commonly temporalis muscle transfer), microsurgical free muscle transfer, and nonsurgical adjuvants used to balance facial symmetry. Each approach has advantages and disadvantages along with ongoing controversies and should be individualized for each patient. Treatments for patients with facial paralysis continue to evolve in order to restore the complex psychomotor process of facial expression.